SANCTIONS FOR EXPLOITATION OF STREET CHILDREN IN ARTICLE 76 (i) OF LAW NO. 35 OF 2014 CONCERNING CHILD PROTECTION IN THE CITY OF BANDUNG FROM THE PERSPECTIVE OF ISLAMIC CRIMINAL LAW - Sari, Winda Widya; Khosim, Ali; Najmudin , Deden (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Economic exploitation of street children is a serious crime in the city of Bandung. In 2022, cases of exploitation of children were still quite high, but experienced a significant decrease from 2022 to 2024. This is inseparable from the efforts of the Bandung City Social Service which runs a rehabilitation program for victims and provides education to the perpetrators. This research was conducted in three regions, namely Asia Africa, Braga, and Gede Bage. Acts of economic exploitation of children are prohibited in Article 76(i) of Law Number 35 of 2014 concerning Child Protection. Sanctions against the perpetrators are regulated in Article 88 of the same law, with a maximum threat of 10 years in prison and a fine of Rp200,000,000. This study uses a descriptive method of analysis with a normative juridical approach. The type of data used is qualitative with primary data sources in the form of observations and interviews, as well as secondary data in the form of journals, books, articles, office reports, and photo documentation. Factors that cause economic exploitation in children include family economic conditions, social environment, and weak supervision. From the perspective of Islamic Law, the perpetrator can be subject to ta'zir sanctions determined by ulil amri. The impact includes a loss of security, disruption of education, reduced playing time, and the formation of deviant characters